Feasibility, complications, morbidity, and mortality results at 6 months for aneurysm treatment with the Flow Re-Direction Endoluminal Device: report of SAFE study. (19th January 2018) - Pierot, Laurent; Spelle, Laurent; Berge, Jérôme; Januel, Anne-Christine; Herbreteau, Denis; Aggour, Mohamed; Piotin, Michel; Biondi, Alessandra; Barreau, Xavier; Mounayer, Charbel; Papagiannaki, Chrisanthi; Lejeune, Jean-Paul; et al.
Abstract : Background and purpose: Flow diverters are increasingly used for the treatment of intracranial aneurysms. Evaluation of the first devices available for clinical use showed high efficacy of this treatment although safety results were worse compared with coiling or balloon-assisted coiling. The S afety and Efficacy A nalysis of F RED E mbolic Device in Aneurysm Treatment (SAFE) trial is a single-arm, multicenter, prospective study conducted to precisely analyze the safety and efficacy of the FRED and FRED Jr devices. Methods: Unruptured and recanalized aneurysms located in the anterior circulation treated with FRED and FRED Jr were prospectively included. Adverse events were independently evaluated by a Clinical Event Committee with a vascular neurosurgeon and an interventional neuroradiologist. Primary safety outcome measures were morbidity and mortality rates at 6 months after treatment. Results: A total of 103 patients/aneurysms were included in 13 interventional neuroradiology (INR) centers. Aneurysm locations were supraclinoid internal carotid artery (ICA) in 71 (68.9%), cavernous ICA in 15 (14.6%), anterior cerebral artery or anterior communicating artery in nine (8.7%), and middle cerebral artery in eight (7.8%). Aneurysms were small (<10 mm) in 71 patients (68.9%). Treatment was successfully performed in 98/103 patients (95.1%). Thromboembolic (TE) complications occurred in 5/103 patients (4.9%), intraoperative rupture in 2/103 patients (1.9%), delayed aneurysm rupture in 1/103 patient (1.0%), and delayed hematoma occurred in 1/103 patient (1.0%). Six-months' mortality and morbidity rates were 1/102 (1.0%) and 2/102 (2.0%), respectively. Conclusions: Aneurysm treatment with the FRED device is safe with low mortality (1.0%) and morbidity (2.0%). Clinical trial registration: NCT02921698 .